(untitled) (Journal of Comparative & International Higher Education, 2022)
International students contribute to the academic and cultural life of universities yet often face discrimination and isolation. Studies highlight that support from the host students can make the difference between an easy or difficult transition. This article is part of a larger project about host student perceptions of international students. Initial analysis indicated that social interactions among international and host students do not become intertwined informally and work best through planned interventions. During the pandemic institutions transitioned from face-to-face to online learning using zoom. We noticed a marked increase in interaction among students online and returned to our research participants to enquire what differences online learning had made to their intercultural experiences. This study focuses on the impact of Virtual Classrooms (VCs) on intercultural relationships, and shows that Zoom offers a platform for increased interaction than face-to-face classrooms.